Sea cucumber protein hydrolysate restores the Th1/Th2 paradigm in cyclophosphamide-induced immunosuppressed mice - Farooqui, Nabeel Ahmed; Rehman, Ata Ur; Khan, Asif Iqbal; Ullah, Hidayat; Ali, Muhsin; Yousuf, Waleed; Alioui, Yamina; Atta, Aamna; Abusidu, Mohammad; Saleh, Bilal; Ghaleb, Eslam; Li, Yanxia; et al. (Frontiers in Nutrition, 2026)
IntroductionImmunocompetence reflects the immune system’s capacity to mount effective responses against antigens. Cyclophosphamide (CYP), a chemotherapeutic and experimental immunosuppressive agent, disrupts T-helper (Th)1/Th2 balance and compromises immune organ integrity. Bioactive peptides derived from the sea cucumber Apostichopus japonicus, which is rich in type I collagen, have shown emerging immunomodulatory potential.MethodsA collagenase-derived sea cucumber protein hydrolysate (SCPH) was prepared using Clostridium collagenase-I and characterized for amino acid composition and peptide profiles. BALB/c mice were administered CYP (80 mg/kg, i.p.) to induce immunosuppression, followed by oral SCPH treatment. Body weight, spleen and thymus indices, leukocyte counts, Th1/Th2-associated gene expression (IFNG, TBX21, IL4, GATA3), serum cytokines and immunoglobulins, and splenic histology and immunohistochemistry were evaluated.ResultsCYP treatment induced body weight loss, reduced immune organ indices, altered leukocyte profiles, and disrupted Th1/Th2-associated markers. SCPH administration partially reversed these changes by restoring spleen and thymus indices, normalizing circulating immune cell levels, upregulating Th1-associated genes (IFNG, TBX21), and downregulating Th2-associated genes (IL4, GATA3). SCPH also increased serum Th1 mediators (IFNG, IgG, IgM) while reducing Th2-associated markers (IL-4, IL-10, IgA, sIgA). Histological and immunohistochemical analyses confirmed improved splenic architecture with elevated T-bet and reduced GATA3 expression.Discussion/conclusionThese findings indicate that SCPH promotes Th1-biased immune rebalancing in CYP-induced immunosuppressed mice, suggesting its potential as a marine-derived immunonutritional agent. Further mechanistic studies are warranted to explore its therapeutic and translational applications.